PECULIARITIES OF CYTOKINE PROFILE CHANGES UNDER THE CONDITIONS OF EXPERIMENTAL PERIODONTITIS AND IMMOBILIZATION STRESS FORMATION AND ITS PHARMACOLOGICAL CORRECTION - Olekshij, P.V.; Hayduchok, I.H.; Regeda-Furdychko, M.M.; Kolishetska, M.A.; Regeda, S.M.; Shnaider, S.A.; Dorosh, I.V. (World of Medicine and Biology, 2023)
The study was devoted to establishing the character of the disturbances content level of TNF-α, IL-6 and IL-10 in the serum of guinea pigs under the conditions of experimental periodontitis and immobilization stress and to evaluate the effectiveness of the thiocetam use. Experimental studies were performed on 50 guinea pigs, which were divided into three groups. The concentration of IL-6, IL-10 and TNF-α in the blood serum was determined. Experimental combined pathology was accompanied by a gradual and significant increase in the blood content of TNF-α and IL-6 with the highest degree of manifestation on day 15 of the experiment and significant depletion of anti-inflammatory cytokine, indicating a significant predominance of proinflammatory activity of the cytokine profile. The administration of thiocetam had a positive effect on the cytokine profile and contributed to a decrease in the proinflammatory cytokine link and a significant increase in the level of interleukin-10 under conditions of experimental periodontitis and immobilization stress.
Keywords: experimental periodontitis; immobilization stress; tumor necrosis factor-α; interleukin-6; interleukin-10; thiocetam